Implementation of an emergency department atrial fibrillation and flutter pathway improves rates of appropriate anticoagulation, reduces length of stay and thirty-day revisit rates for congestive heart failure. Issue 3 (9th November 2017) - Barbic, David; DeWitt, Chris; Harris, Devin; Stenstrom, Robert; Grafstein, Eric; Wu, Crane; Vadeanu, Cristian; Heilbron, Brett; Haaf, Jenelle; Tung, Stanley; Kalla, Dan; Marsden, Julian; et al.
Abstract: Objectives: An evidence-based emergency department (ED) atrial fibrillation and flutter (AFF) pathway was developed to improve care. The primary objective was to measure rates of new anticoagulation (AC) on ED discharge for AFF patients who were not AC correctly upon presentation. Methods: This is a pre-post evaluation from April to December 2013 measuring the impact of our pathway on rates of new AC and other performance measures in patients with uncomplicated AFF solely managed by emergency physicians. A standardized chart review identified demographics, comorbidities, and ED treatments. The primary outcome was the rate of new AC. Secondary outcomes were ED length of stay (LOS), referrals to AFF clinic, ED revisit rates, and 30-day rates of return visits for congestive heart failure (CHF), stroke, major bleeding, and death. Results: ED AFF patients totalling 301 (129 pre-pathway [PRE]; 172 post-pathway [POST]) were included; baseline demographics were similar between groups. The rates of AC at ED presentation were 18.6% (PRE) and 19.7% (POST). The rates of new AC on ED discharge were 48.6 % PRE (95% confidence interval [CI] 42.1%-55.1%) and 70.2% POST (62.1%-78.3%) (20.6% [ p <0.01; 15.1-26.3]). Median ED LOS decreased from 262 to 218 minutes (44 minutes [ p <0.03; 36.2-51.8]). Thirty-day rates of ED revisits for CHF decreased from 13.2% to 2.3% (10.9%; p <0.01; 8.1%-13.7%), and rates of other measures were similar. Conclusions: The evidence-based pathway led to an improvement in the rate of patients with new AC upon discharge, a reduction in ED LOS, and decreased revisit rates for CHF. RÉSUMÉ: Contexte: Un nouveau parcours de traitement de la fibrillation auriculaire et du flutter (FAF) au service des urgences (SU), fondé sur des données probantes a été élaboré afin d'améliorer la prestation de soins. L'étude avait pour objectif principal de mesurer le taux de nouvelle anticoagulation (AC) au moment du congé du SU chez des patients atteints de FAF mais non soumis à une anticoagulation appropriée au moment de la consultation. Méthode: Il s'agit d'une étude d'évaluation de type avant-après, menée d'avril à décembre 2013, qui visait à mesurer l'incidence du parcours de traitement sur le taux de nouvelle AC et sur d'autres mesures de rendement chez des patients atteints de FAF sans complications et traités seulement par des médecins d'urgence. La collecte de données démographiques et de renseignements sur les maladies concomitantes et les traitements prescrits au SU a été réalisée à l'aide d'un examen uniformisé de dossiers. Le principal critère d'évaluation consistait en le taux de nouvelle AC. Les critères secondaires d'évaluations comprenaient la durée de séjour (DS) au SU, l'orientation vers un centre de traitement de la FA et du flutter, le taux de reconsultation au SU et le taux de reconsultation au bout de 30 jours pour de l'insuffisance cardiaque (ICC), un accident vasculaire cérébral, une hémorragie importante ou la mort. Résultats: Au total, 301 patients atteints de FAF et traités au SU (129 avant le parcours et 172 après le parcours) ont été retenus dans l'étude; les données démographiques de base étaient comparables dans les deux groupes. Les taux d'AC au moment de la consultation au SU étaient de 18, 6 % et de 19, 7 % avant et après le parcours respectivement, et les taux de nouvelle AC au moment du congé du SU, de 48, 6 % (IC à 95 % : 42, 1-55, 1 %) et de 70, 2 % (62, 1-78, 3 %) (20, 6 % [ p <0, 01 : 15, 1-26, 3]) respectivement. La DS médiane au SU est passée de 262 minutes à 218 (44 minutes [ p <0, 03 : 36, 2-51, 8]) et le taux de reconsultation au SU au bout de 30 jours pour de l'ICC, de 13, 2 % à 2, 3 % (10, 9 %; p <0, 01 : 8, 1-13, 7 %). Le taux des autres mesures était similaire. Conclusions: Le parcours de traitement fondé sur des données probantes s'est traduit par une amélioration du taux de nouvelle AC au moment du congé, une réduction de la DS au SU et une diminution du taux de reconsultation pour de l'ICC.